2018
DOI: 10.3390/molecules23040880
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of the Pleurotus ostreatus Laccase Gene (PoLac) Family and Functional Characterization of PoLac2 Involved in the Degradation of Cotton-Straw Lignin

Abstract: Fungal laccases play important roles in the degradation of lignocellulose. Although some PoLacs have been reported in several studies, still no comprehensive bioinformatics study of the LAC family in Pleurotus ostreatus has been reported. In this study, we identified 12 laccase genes in the whole genome sequence of P. ostreatus and their physical characteristics, gene distribution, phylogenic relationships, gene structure, conserved motifs, and cis-elements were also analyzed. The expression patterns of 12 PoL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 58 publications
2
41
0
Order By: Relevance
“…The construction of genetically modified strains is an alternative way to improve the laccase yield of SSF. Overexpression of homologous or heterologous genes encoding laccase and related ligninolytic enzymes may increase the utilization rate of lignocellulosic wastes and improve laccase production [108]. In addition, heterologous expression of thermostable laccase in a thermotolerant white rot fungi provides good potential for large-scale production of laccase by SSF.…”
Section: Fungal Strains Effective For Laccase Production From Agriculmentioning
confidence: 99%
“…The construction of genetically modified strains is an alternative way to improve the laccase yield of SSF. Overexpression of homologous or heterologous genes encoding laccase and related ligninolytic enzymes may increase the utilization rate of lignocellulosic wastes and improve laccase production [108]. In addition, heterologous expression of thermostable laccase in a thermotolerant white rot fungi provides good potential for large-scale production of laccase by SSF.…”
Section: Fungal Strains Effective For Laccase Production From Agriculmentioning
confidence: 99%
“…We observed that laccase genes in the same group had a similar number of introns. For example, AaLac7 and AaLac8 are more closely related to the PoLac2 gene from P. ostreatus , and these genes all had complex intron-exon structures [ 51 ]. We also found that the structures of AaLac10 and AaLac12 were distinct from other laccase genes of A. areolatum , and exhibited high homology with the CcLac16 and CcLac17 genes from C. cinerea [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exon theory suggested that the number and distribution of introns are related to gene evolution [ 55 ]. Thus, the more complex intron-exon structures seen in some of the laccase genes may indicate their later emergence, as over evolutionary time, introns reorder, leading to the fusion of exons to create more complex genes [ 51 , 55 ]. Analysis of the characteristics of the identified A. areolatum laccase proteins showed that, except for AaLac3, all laccases have signal peptides and no transmembrane region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to meet laccase production levels for industrial applications, laccase overexpression into native hyper-producer strains should be more extensively studied as an alternative to decrease laccase cost production. Pleurotus ostreatus, Polyporus brumalis and Gloeophyllum trabeum fungal strains have been transformed for laccase homologous overexpression by different methods [78][79][80]. The constitutive overexpression of laccase in P. brumalis under the control of the glyceraldehyde-3-phosphate dehydrogenase promoter increased laccase activity 4 times higher than that of the wild-type strain [79].…”
Section: Fermentation Yields Of Native and Recombinant Laccase-producersmentioning
confidence: 99%